Turbulence damping above the cloud height in suspensions of concentrated slurries in stirred tanks. Issue 7 (9th February 2021) - Ayranci, Inci; Kresta, Suzanne M.
Abstract: Poor mixing in the clear liquid layer above the cloud height has been reported by several authors. This study uses LDV measurements to quantify turbulence above the cloud using a liquid level of 1.5 T to remove the barrier of a free surface at H  =  T . A D  =  T /3, down‐pumping PBT was used at an off‐bottom clearance of C  =  T /3. Three slurries were tested at impeller speeds 0.8, 1, and 1.2 N js . The change in turbulence was quantified using the normalized root mean square (RMS) of the fluctuating velocity summed and averaged over each radial traverse. A significant difference between the fluctuating values of the cloud height—minimum, average, and maximum—was observed. The turbulence decays until the maximum cloud height. Beyond that, it remains constant and near zero. The effects of both particle size and solids concentration prove to be important.